2022
DOI: 10.1371/journal.pone.0270144
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of excess high-fructose corn syrup on the DNA methylation of hippocampal neurotrophic factor in childhood and adolescence

Abstract: Consumption of fructose-containing beverages such as high-fructose corn syrup (HFCS) is increasing, raising concerns about the negative effects of excessive fructose intake. A recent report indicated that excess HFCS intake impairs hippocampal function. In this study, we focused on neurotrophic factors (NFs) in the hippocampus from the viewpoint of epigenetics to clarify the adverse effects of fructose. We analyzed the effects of HFCS intake on hippocampal function in three age categories: childhood and adoles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Inattention and impulsivity are two of the main characteristics of attention-deficit/hyperactivity disorder (ADHD) [ 168 ], stipulated as diagnostic criteria in the DSM-IV [ 169 ], and previously linked to diet in human studies [ 170 ]. Some age cohort studies found no impact of added sugars on hippocampal brain-derived neurotrophic factor (BDNF) in adult rats where significant alterations were found subsequent to childhood and adolescent SSB intake [ 50 , 60 ]. These results highlight a critical period of increased susceptibility to adverse effects due to sugar consumption, making perinatal, childhood, and adolescence a period of particular vulnerability.…”
Section: Introductionmentioning
confidence: 99%
“…Inattention and impulsivity are two of the main characteristics of attention-deficit/hyperactivity disorder (ADHD) [ 168 ], stipulated as diagnostic criteria in the DSM-IV [ 169 ], and previously linked to diet in human studies [ 170 ]. Some age cohort studies found no impact of added sugars on hippocampal brain-derived neurotrophic factor (BDNF) in adult rats where significant alterations were found subsequent to childhood and adolescent SSB intake [ 50 , 60 ]. These results highlight a critical period of increased susceptibility to adverse effects due to sugar consumption, making perinatal, childhood, and adolescence a period of particular vulnerability.…”
Section: Introductionmentioning
confidence: 99%
“…Kidney tissues were homogenized using radio-immunoprecipitation assay buffer (Wako Pure Chemicals, Osaka, Japan). Sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) and Western blotting were performed as described previously [24]. The primary antibodies against 5α-Red1 (Abcam, Cambridge, UK), 11β-HSD2 (Proteintech, Rosemont, USA), and β-actin (Abcam, located in Cambridge, UK) were used.…”
Section: Western Blottingmentioning
confidence: 99%
“…The exact mechanisms by which fructose modifies urine composition are still not completely understood and a specific epigenetic mechanism exerted by fructose in nephrolithiasis or risk factors for kidney stone formation have not been described. However, from available data, we know that fructose acts via epigenetic mechanisms (ncRNA and DNA methylation) in other conditions [ 57 , 58 , 59 ], such as nonalcoholic fatty liver disease (NAFLD) [ 60 , 61 , 62 ]. Therefore, we can speculate that fructose might act via epigenetic mechanisms to regulate the expression of genes that encode crucial transporters of anti- and prolithogenic urinary molecules.…”
Section: Food Compoundsmentioning
confidence: 99%